Young people's expectations of and satisfaction with transitional care from paediatric and adult care perspectives. (29th September 2015) - Watanabe, A; Shaw, K; Rankin, E; McDonagh, J
Abstract : Transitional care is now embedded into national health policy and has recently been specifically highlighted as a key area for attention in the forthcoming review of children's services by Sir Ian Kennedy. Aims: To examine young people's expectations of and satisfaction with transitional care in paediatric and adult settings. Methods: Young people aged 11–21 years with a chronic condition diagnosed under 19 years of age requiring long-term follow-up in secondary care were recruited from specialty clinics (n=17) in a paediatric hospital and it's neighbouring adult facility. Expectations of and satisfaction with healthcare delivery were assessed using the self-completed "Mind the Gap" questionnaire which measures the gap between the adolescent's expectation of best care and their perception of the actual service provided. The response format is a seven-point Likert scale anchored by "strongly disagree" at one and "strongly agree" at seven. The scale measures three dimensions of healthcare: environment, provider characteristics and process issues. Results: 247 young people participated in the study, 157 (median age 15.04 years range 11.17–20.42) in the paediatric clinics and 95 (median age 19.58, range 17.17–21.92) in the adult clinics. There were no significant differences between the overall satisfaction and the three dimensions between the young people in the paediatric setting when compared to the adult setting. All participants rated provider characteristics as most important and environment as least important. Ratings of current service delivery were significantly lower than young people's expectations. Young people were least satisfied with the environment and most satisfied with health provider characteristics. Young people rated health provider's knowledge of the young person's condition including latest treatments, and their honesty as the most essential aspects of best practice. Conclusions: The significant gap between young people's expectations of best care and their perception of the actual service provided in all domains in both settings suggests further improvement in transitional care delivery is needed by both paediatric and adult care providers. Since provider characteristics are most important to young people, support and investment for continuous professional development for staff is integral to young person friendly transitional care services.